Correlation between serum leptin concentration and disease activity in normal body mass index premenopausal women with systemic lupus erythematosus - Suarjana, I Nyoman; Kasjmir, Yoga I; Isbagio, Harry; Soegondo, S (Indonesian Journal of Rheumatology, 2009)
Background. Leptin is recognized as a cytokine-like hormone with pleiotropic actions in modulating immune responses. The role of leptin in pathogenesis of systemiclupus erythematosus (SLE) was not fully understood yet. Previous study did not fi nd the correlation between serum leptin concentration and disease activity in patients with SLE, but selection of the subjects wasnât based on the classifi cation of body mass index (BMI) and menopausal status.Objective. To determine correlation between serum leptin concentration and the disease activity in normal BMI premenopausal women with SLE.Methods. Serum leptin concentration was measured by enzyme-linked immunosorbent assay and disease activity was scored using Mexican SLE disease activity index (Mex-SLEDAI). Spearmanâs correlation coeffi cient test was used for evaluating the strength of association between leptin level and Mex-SLEDAI score.Results. Seventy normal BMI premenopausal women with SLE were included in this study. The median of serum leptin concentration was 13.4 (0.6 â 45.9) ng/ml.The median serum leptin concentration in patients with active disease was 12.4 (0.6 â 41.6) ng/dl, whereas in patients with inactive disease was 15.2 (3.9 â 45.9) ng/dl.No signifi cant different was found between serum leptin concentration in active and inactive disease (p = 0.14). A weak negative correlation was observed between leptinconcentration and Mex-SLEDAI score, but not statistically signifi cant (r = -0.22; p = 0.07).Conclusion. No correlation was found between serum leptin concentration and disease activity in normal BMI premenopausal women with SLE. Prednisone doses anddisease duration might interfere.